Pengaruh Produk Dan Promosi Terhadap Keputusan Pembelian Konsumen Handphone Vivo Pada Counter Semaku Ponsel Manna Bengkulu Selatan - Al Munif; Wagini Wagini; Ida Ayu Made Ermeytha G (Jurnal Multidisiplin Dehasen (MUDE), 2024)
Product quality is a product's ability to meet every consumer need in accordance with the needs and desires of consumers and promotion is an effort to offer products or services with the aim of attracting potential consumers to buy a product. This thesis is entitled “The Influence of Products and Promotions on Consumer Purchasing Decisions for Vivo Handphone at Semaku Cellphone Counter Manna of South Bengkulu. This study aims to determine the effect of products and promotions on consumer purchasing decisions for Vivo Handphone at Semaku Cellphone Counter Manna of South Bengkulu. This study uses quantitative research, the object of research is all consumers who come to buy Vivo Handphone Semaku Cellphone Counter Manna of South Bengkulu. The sampling method uses a non-probability sampling method where the proportional sampling method is a method of determining the sample through considerations and criteria that deserve to be sampled, namely 65 respondents. The data collection technique used a questionnaire instrument. The data processing technique used is data processing with SPSS version 29. The value of the product variable t count 6.529 is greater than t table 0.244, the value of the promotion t count 4.312 is greater than t table of 0.244. The results of F test with a significant value of product and promotion variables of 0.01<alpha 0.05 and the calculated F count 612.554 is greater than F table 3.31. This shows that the independent variables together have an influence on purchasing decisions with a coefficient of determination of 0.295 (29.5%) and the remaining 70.5% is influenced by other factors not included in this study.